2012
DOI: 10.1002/hed.22907
|View full text |Cite
|
Sign up to set email alerts
|

CO2 laser surgery in elderly patients with glottic carcinoma: Univariate and multivariate analyses of results

Abstract: Even in elderly patients with early glottic carcinoma, endoscopic laser surgery is an effective treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 44 publications
3
16
1
Order By: Relevance
“…One study of 810 elderly surgical head and neck cancer patients found perioperative mortality rates as low as 3.5% . Additional positive outcomes have been demonstrated specifically at the laryngeal subsite and with combined head and neck cancer treatment modalities, where elderly patients exhibited a clinically positive response to aggressive treatment . Our work confirms the positive outcome of surgery, because we observed a substantial increase in survival for elderly patients who received surgery compared to those who did not.…”
Section: Discussionsupporting
confidence: 83%
“…One study of 810 elderly surgical head and neck cancer patients found perioperative mortality rates as low as 3.5% . Additional positive outcomes have been demonstrated specifically at the laryngeal subsite and with combined head and neck cancer treatment modalities, where elderly patients exhibited a clinically positive response to aggressive treatment . Our work confirms the positive outcome of surgery, because we observed a substantial increase in survival for elderly patients who received surgery compared to those who did not.…”
Section: Discussionsupporting
confidence: 83%
“…According to our search criteria, 832 papers were initially identified. After sorting and removal of duplicates, only four papers that fully fit our inclusion criteria were retrieved and reviewed in detail . One of these studies was discarded because it included patients treated with open partial laryngectomy and total laryngectomy.…”
Section: Resultsmentioning
confidence: 99%
“…Because no correlations emerged between age and exposure variables, it may be that the tumor has a less aggressive behavior in older people, but further studies with a tailored design are needed to investigate this issue. On the other hand, primary TLM has already proved to be a safe and effective treatment for glottic cancer in elderly patients …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, primary TLM has already proved to be a safe and effective treatment for glottic cancer in elderly patients. 26…”
Section: Discussionmentioning
confidence: 99%